Sustained growth of the Southern Ocean carbon storage in a warming climate. Issue 11 (4th June 2015) - Ito, Takamitsu; Bracco, Annalisa; Deutsch, Curtis; Frenzel, Hartmut; Long, Matthew; Takano, Yohei
Abstract We investigate the mechanisms controlling the evolution of Southern Ocean carbon storage under a future climate warming scenario. A subset of Coupled Model Intercomparison Project Phase 5 models predicts that the inventory of biologically sequestered carbon south of 40°S increases about 18–34 Pg C by 2100 relative to the preindustrial condition. Sensitivity experiments with an ocean circulation and biogeochemistry model illustrates the impacts of the wind and buoyancy forcings under a warming climate. Intensified and poleward shifted westerly wind strengthens the upper overturning circulation, not only leading to an increased uptake of anthropogenic CO2 but also releasing biologically regenerated carbon to the atmosphere. Freshening of Antarctic Surface Water causes a slowdown of the lower overturning circulation, leading to an increased Southern Ocean biological carbon storage. The rectified effect of these processes operating together is the sustained growth of the carbon storage in the Southern Ocean, even under the warming climate with a weaker global ocean carbon uptake.